Ultrasound‐guided saphenous and sciatic nerve block as part of multimodal pain management in a goat undergoing tibial fracture repair. Issue 1 (3rd January 2022) - Ferrero, Camilla; Klonner, Moriz Ettore; Verdier, Natali; Bradbrook, Carl
Abstract: A 6‐week‐old goat was presented for surgical repair of a Salter Harris type 1 fracture of the right tibia. The goat was premedicated with butorphanol 0.2 mg/kg and midazolam 0.2 mg/kg intramuscularly, followed by induction of anaesthesia with ketamine 1 mg/kg and propofol 3.2 mg/kg intravenously. Anaesthesia was maintained with isoflurane in an oxygen air mix. An ultrasound‐guided saphenous and sciatic nerve block was performed using 0.1 ml/kg/nerve of ropivacaine 0.75%. Except for a slight gradual decrease in arterial blood pressure, all monitored variables remained within accepted ranges throughout surgery. No additional intraoperative analgesia was required. Recovery from anaesthesia was uneventful and the goat started drinking milk 5 minutes after extubation. Buprenorphine 0.02 mg/kg intramuscularly was administered in the evening and repeated 12 hours after the first dose. Additionally, carprofen 1.4 mg/kg intramuscularly was administered every 48 hours for the following days. The goat was discharged 2 days after surgery.